Part of the solution or part of the problem? Reflections on teaching participatory asset mapping - Parker, Jonathan; Crabtree, Sara Ashencaen (Oxford University Press, 2016)
Community asset mapping is widely employed in a diverse range of community development programmes, including work with indigenous groups. Here we discuss the outcome of a participatory asset mapping training programme we were asked to deliver for social and community work students and academics at a university in Peninsular Malaysia. The attendees were planning imminent intervention work with the indigenous Orang Asli communities of Tasik Chini, Pahang, Malaysia, with whom we were undertaking our own separate research at the time. The underpinning philosophy and approach of participatory asset mapping is discussed in terms of its use in the community context. A self-reflexive analysis of research relationships and trainer responsibilities is explored in this discursive, conceptual article